Visual assessment on product label design criteria through eye tracking - Mohd Hafiz Faizal Mohamad Kamil,; Azizah Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Product label is a printed product information displayed on the product packaging. The product label designs are the combination of text and image elements. The process of designing a product label is complicated as there are various types of text and images involved. Product label designs that are less attractive wouldl affect purchasing choices. The purpose of this study is to identify the design criterias of texts and images to help consumer in their purchase selection. The study focuses on the visual assessment through eye tracking method on food and beverage product label. The eye movement observation method conducted using eye tracker device to track 6 parameters of eye movements on the product label during purchasing selection and determine 7 main text and image design criterias for food and beverage product label. The consumers were selected among university students. The study has found that the purchase selection of bread and mineral water product from the food and beverage product category are the most difficult. There are similarities in eye tracking parameters on product label visual assessment during purchasing choices. The similarities of text and image design criteria on food and beverage products label include i) shape text: uppercase and lowercase, ii) type family text: sanserif, iii) width text: condensed, iv) slope text: roman, v) weight text: bold and vi) nature image: illustration.